Determining the optimum culture's conditions for protease production from Metarhizium anisopliae - Mohammed Reddah Annon; Muna Ibrahim Jasim (Al-Qadisiyah Journal of Pure Science, 2018)
The identify optimum conditions for protease production from Metarhizium anisopliae and the maximum yield was in the medium contain Date syrup (DS) at concentration 0.05 % as carbon sources and supplemented with 0.5 % gelatin as nitrogen sources , the inoculum size was 16 % at initial pH 5.5 after 72 h from incubation with rotary shaker at 100 rpm at the temperature 30 ËšC .